Carbazole alkaloids with bioactivities from the stems of Clausena lansium. (August 2020) - Sun, Xing-Yan; Ma, Jie; Li, Chuang-Jun; Zang, Ying-Da; Huang, Ji-Wu; Wang, Xu-Yan; Chen, Nai-Hong; Chen, Xiao-Guang; Zhang, Dong-Ming
Graphical abstract: Highlights: Four undescribed carbazole alkaloids were obtained from the stems of Clausena lansium . The absolute configuration of claulansine U was defined by a single-crystal X-ray diffraction analysis. Compounds 1 and 2 protected PC12 cells against serum deprivation injury at 10 μM. Compound 4 showed obvious cytotoxicities against MCF-7, HCT-116, HepG2, Capan2 cancer cell lines with IC50 values at 2.23, 2.16, 3.23, and 4.94 μM. Abstract: Four unreported carbazole alkaloids named as claulansines U – W (1, 2, 4 ), (–) -(2′ R )-claulamine A (3b ) and one known analogue, claulamine A (3a ) were obtained from the stems of Clausena lansium . Their structures were demonstrated by spectroscopic experiments. The absolute configuration of claulansine U (1 ) was determined by single-crystal X-ray diffraction analysis. Compounds 1 and 2 protected PC12 cells against serum deprivation injury at 10 μ M — an increase of cell survival rates from 47.4 ± 4.3 % (model) to 67.8 ± 6.6 % and 63.3 ± 8.2 %, respectively. And compound 4 showed significant cytotoxicities to four human cancer cell lines, with IC50 values ranging from 2.16 to 4.94 μ M.